Incarceration and Family Stress as Understood through the Family Process Theory: Evidence from Hong Kong - Chui, Wing Hong (Frontiers in Psychology, 2016)
The myriad of negative effects brought about by the incarceration of a family member have consistently been demonstrated in research. However, previous works have tended to focus on the perspectives of family members separately, rather than exploring the dynamic relationships within the family as an entire unit. Moreover, such research is still limited in the Chinese cultural context. Thus, the current study aimed to examine the applicability of the Family Process Theory on a small sample of Chinese fathers who were imprisoned and have returned to their communities, conceptualizing the challenges faced by their families under the theoretical elements of rules of transformation, rituals, ambiguous loss and boundary ambiguity. A total of 17 participants were recruited through the assistance of service organizations, and data were collected via semi-structured interviews. As congruent with the theory, inmates’ families were found to come across problems particularly in the transitioning phase and establishment of new rituals, while ambiguity surrounding the incarceration and the blurred role of the father led to problems with fatherhood identity both during and after the incarceration. Recommendations are made, in line with these findings and the suggestions of ex-prisoners, for services to have more of a focus on preserving the integrity of inmates’ families. Given the right circumstances, families can even serve as a motivator for incarcerated fathers to improve themselves and mature, leveraging the important supportive role of the family and the fear of again being separated from one’s family as effective deterrents to recidivism.